Implementasi Peraturan Daerah Kota Magelang Nomor 8 Tahun 2020 tentang Penyediaan, Penyerahan, dan Pengelolaan Prasarana, Sarana, dan Utilitas Umum Perumahan dan Kawasan Permukiman - Rachmawati, Intan; Madalina, Maria (Res Publica: Jurnal Hukum Kebijakan Publik, 2022)
This legal research analyzes and examines, first, whether the implementation of Magelang City Regional Regulation Number 8 of 2020 on the Provision, Delivery, and Management of Infrastructure, Facilities, and Public Utilities for Housing and Settlement Areas in Magelang City is in accordance with the laws and regulations. with the laws and regulations. Second, related to factors that hinder and efforts that can be made in implementation of Magelang City Regional Regulation Number 8 of 2020 concerning Provision, Delivery, and Management of Infrastructure, Facilities, and Public Utilities of Housing and Settlement Areas in Magelang City is in accordance with the laws and regulations. Public Utilities of Housing and Settlement Areas in Magelang City. The result of This legal research shows that the implementation of Local Regulation Magelang City Regulation Number 8 of 2020 on the Provision, Delivery, and Management of Infrastructure, Facilities, and Public Utilities of Housing and Settlement Area Settlement Areas is currently in the process of implementing the DPRD's target. Factors influencing inhibiting factors are related to site plan, ownership, and included in new legal products.